Fasting of the bit-logarithmic code calculations for additional- multiplication operators - Гамаюн, В. П.; Андрєєв, А. А.; Чайка, М. П. (Problems of Informatization and Control, 2009)
The model arithmetic basic operations for bit-logarithmic coding which is guaranteed for transformation increasing diapason data and significant reduce influence of round were considered. Fasting realization basic operations from gradient data location in operation of sorting which is present in each computing operations is suggested